Optimal control of a road racing motorcycle on a three-dimensional closed track. Issue 8 (2nd August 2020) - Leonelli, L.; Limebeer, D. J. N.
Abstract : The primary aim of this work is to validate dynamic minimum-lap-time optimal control simulations for a sports motorcycle on a 3D track. The racing line and rider inputs are optimised, while recognising the geometric features of a three-dimensional (3D) closed-circuit track, which is described in terms of curvilinear coordinates. A simple vehicle model is developed, which includes longitudinal weight transfer effects and a Magic Formula (MF) tyre description. The minimum-lap-time optimal control problem (OCP) is solved using a direct transcription technique that is based on orthogonal collocation. Detailed comparisons are made between experimental data and optimal theoretical predictions. The influences of the 3D features of the track are highlighted and discussed. The minimum-lap-time handling properties of the vehicle are also analysed.